Uveitis and primary lesions disseminated in syphilis - Aires Junior, Luiz Fernando (2007)
Introduction: syphilis is an infectious and contagious illness caused by sexual transmission, which is ascending in the Brazilian public health scenario. Therefore all professionals of the health area must be aware of the manifestations of this illness including extragenital manifestations. Objective: analyzing a clinical case of primary syphilis that was diagnosised from ocular manifestations and disseminated primary injuries. Methods: ophthalmologic and clinical analysis of the injuries of the patient, as well as examinations in laboratories (VDRL, FTA-Abs IgM/IgG, HIV sorology, HBsAg, anti-HBc total, antiHBsAg, anti-HCV) have been conducted. Results: the association of the clinical findings and epidemiologic investigation, with the positive result of VDRL, with FTA-Abs IgM in a no-HIV patient, confirmed the diagnostic hypothesis of primary syphilis. Conclusion: it is of utmost importance for health professionals, to gather new references of the knowledge of other manifestations of syphilis, in order to be able to establish a correct diagnosis and treatment, and avoid complications.